1993
DOI: 10.1021/ma00053a017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of structure formation at the microphase separation transition in diblock copolymers

Abstract: Time-resolved small-angle X-ray scattering is used to investigate the time dependence of structure formation at the ordering transition in bulk diblock copolymers. After a quench from the disordered into the ordered state two relaxation processes are found on well-separated time scales. The slow process displays an unusual temperature dependence and is discussed as a nucleation phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 6 publications
5
36
1
1
Order By: Relevance
“…[10][11][12][13][14] The observed nucleation and growth process agrees well to the weak first-order nature of the isotropic-to-lamellar phase transition predicted by Fredrickson and Helfand under consideration of the fluctuation correction to the mean-field theory. [10][11][12][13][14] The observed nucleation and growth process agrees well to the weak first-order nature of the isotropic-to-lamellar phase transition predicted by Fredrickson and Helfand under consideration of the fluctuation correction to the mean-field theory.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…[10][11][12][13][14] The observed nucleation and growth process agrees well to the weak first-order nature of the isotropic-to-lamellar phase transition predicted by Fredrickson and Helfand under consideration of the fluctuation correction to the mean-field theory. [10][11][12][13][14] The observed nucleation and growth process agrees well to the weak first-order nature of the isotropic-to-lamellar phase transition predicted by Fredrickson and Helfand under consideration of the fluctuation correction to the mean-field theory.…”
Section: Introductionsupporting
confidence: 83%
“…It generally exhibits three regimes. [10][11][12][13][14] In thermally activated nucleation Morphology evolution reveals that the lamellar domains grow from nucleation sites, bearing some similarities with crystallization.…”
Section: Ordering Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the static properties have been studied extensively, much less attention has been devoted to the kinetics near the microphase separation [6,7]. The first rheological study [6] on the ordering kinetics was made on the system PEP-PEE and revealed a narrow temperature range below the order-disorder temperature T o D T within which the ordering process can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Structure formation in block copolymers has been extensively studied from both theoretical and experimental view points [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In block copolymers composed of only amorphous components, the driving force for structure formation is the incompatibility between the block chains, characterized by c N t , where c is the Flory interaction parameter and N t is the total number of segments in the copolymer.…”
Section: Introductionmentioning
confidence: 99%